1991
DOI: 10.2186/jjps.35.708
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Consciousness of Masticatory Laterality.

Abstract: Abstract:This study was made to investigate the correlation between masticatory laterality, handedness and footedness in 1287 volunteers.The results obtained were as follows: 1. Right-biased chewing behaviour was slightly predominant in comparison with the other side.2. Handedness and footedness had no significant correlation with masticatory laterality. 3. It was showed that oral diseases and the treatments mainly motivated to be conscious of masticatory laterality. Dental caries, toothache and missing teeth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The cause of masticatory laterality has been much discussed and such factors as missing teeth, tooth pain, rampant caries and orofacial pain are considered to be involved (Ueda et al ., 1991). To eliminate these relatively apparent causes, subjects without those factors were chosen.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of masticatory laterality has been much discussed and such factors as missing teeth, tooth pain, rampant caries and orofacial pain are considered to be involved (Ueda et al ., 1991). To eliminate these relatively apparent causes, subjects without those factors were chosen.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that individuals with unilateral missing posterior teeth tended to chew on the side with teeth remaining, indicating that reduced occlusal support due to the loss of teeth is a predominant factor in mastication predominance 15) . For edentulous individuals with complete dentures, factors that may explain the existence of mastication predominance include pain in denture-supporting tissues or other masticatory structures, as well as morphological factors (e.g., severe absorption of mandibular and/or maxillary bone) 17,18) . Further studies are required to investigate this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the frequency of the subjectivity of the habitual chewing side, Ueda et al 42 reported that about half of the subjects were conscious of their habitual chewing side, and Kurachi et al 31 report ed that about threequarters of the subjects were conscious of their habitual chewing side, and this was discovered at the medical interview. Ogimito et al 33 compared the reliability of the subjectivity of the habitual chewing side before and after mas tication, and the results suggested that the medi cal interview after mastication was more reliable and more detectable than the one before.…”
Section: Relationship Between the Subjectivity Of The Habitual Chewinmentioning
confidence: 99%